If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 10 = 36 Reorder the terms: 10 + 4m = 36 Solving 10 + 4m = 36 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 4m = 36 + -10 Combine like terms: 10 + -10 = 0 0 + 4m = 36 + -10 4m = 36 + -10 Combine like terms: 36 + -10 = 26 4m = 26 Divide each side by '4'. m = 6.5 Simplifying m = 6.5
| 23+5x=111-3x | | 7(51)=10 | | -2(3-7)-4= | | x=11+7y | | 2b+b=7 | | 13+3x=3n-29 | | 3y-2=4(2y-3) | | 13+3x=-29-3n | | 2.6=0.2-4 | | -2a+(5a-3)-(3a+4)= | | 8-3k+6k=2k-3 | | -4(x+3)-7=-3x-15 | | 6(w-3)-(2w-5)=3w | | y=-8/9x-8/9 | | -5+7x+7=8(x+3)-9 | | 12R=1/4M-5 | | 4x-28y=44 | | -2y+13=14-y | | g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 | | -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) |